A Semiotica Analysis of The Symbols’ Representation in Market Place As Communication Language - Redho Tri Saputra (Teaching English and Language Learning English Journal, 2022)
The objective of the research was to find out the Symbols’ Representation In Marketplace As Communication Language. The design of this research was descriptive qualitative method. The instrument of the research was is something that is used in doing a work (Ary: 2002). Analysis Roland Barthes' semiotic paradigm. This study will analyze data regarding the meaning of denotation and connotation of symbols in the Tokopedia marketplace application. In this study there are instruments that is, the instrument is a list of symbols that contain meaning and understanding in English which is difficult for ordinary people to understand and very difficult to understand. The results showed understand the understanding of a symbol that is in the market place. In this section the found s everal forms of understanding from each student to the symbols made in the form of questions in the google classroom media, the form of understanding was based on symbols, which the researchers gave to 10 students, some of which were questions in the form of choices from 4 market places. namely Shopee, Tokopedia, Lazada, and Bukalapak.Which were seen from 8 symbols from 4 market place applications. It can be concluded that students' understanding of the symbols given are very helpful in understanding a symbol contained in a market place where the symbol can be a communication tool or communication language for students who do not understand the meaning of the symbol. Key Words: Semiotic, Symbols , Language,Communication